ANALISIS NILAI PERUSAHAAN, KINERJA PERUSAHAAN DAN KESEMPATAN BERTUMBUH PERUSAHAAN TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG LISTING DI BEI - Septy Kurnia Fidhayatin; Nurul Hasanah Uswati Dewi (The Indonesian Accounting Review, 2012)
In the era of globalization of capital markets have a very important role in the economic activitiesof a state. The company is one of the forming of GDP within a state. Investors are oneof important components in the financing activities of a public company, and the return isvery important for investors because investors expect a high return on their infestations. Sothe value of the company, company performance and growth opportunities the company canbe used as benchmarks to know the stock return. The purpose of this study was to determinethe effect of corporate value, corporate performance and the opportunity to grow the companyto stock returns. The samples used in this study were 175 manufacturing companieslisted on the Indonesia Stock Exchange (BEI) in the period 2006-2010. Statistical tests usedwere multiple linier regression tests. Statistic test results indicate that the value of the companyand corporate performance affect stock returns. It can be seen from the F test and t testwhich showed positive results, which means the value of the company and corporate performancesignificantly to stock returns. The opportunity to grow the F test and t test showednegative results, which means that the company did not grow significantly on stock returns.This is because the opportunity to grow a company not only from the increase or decrease infixed assets but because of other factors.